2018
DOI: 10.1042/bsr20180169
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA XIST predicts worse prognosis in digestive system tumors: a systemic review and meta-analysis

Abstract: Increasing studies are indicating that long non-coding RNA (lncRNA) X-inactive specific transcript (XIST) is associated with the prognosis of cancer patients. However, the results have been disputed. Therefore, we aimed to further explore the prognostic value and clinical significance of XIST in various types of cancers. Then, we focussed our research on the comparison of the predictive value of XIST between digestive system tumors and non-digestive system tumors. We performed a systematic search by looking up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Mao et al (21) identified 15 eligible studies containing 1,209 patients for inclusion in their meta-analysis; they observed that increased lncRNA-XIST expression levels in cancer tissues were associated with a poorer overall survival. In the study conducted by Liu et al (22), 15 studies with a total of 920 patients were included in the meta-analysis, and the results suggested that high lncRNA-XIST expression levels were associated with distant metastasis, tumor stage and poor prognosis. However, a number of contrasting studies were published concerning the role of lncRNA-XIST in cancer: In a recent study by Du et al (18), lncRNA-XIST served as a tumor suppressor in prostate cancer, its expression correlating with prognosis and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mao et al (21) identified 15 eligible studies containing 1,209 patients for inclusion in their meta-analysis; they observed that increased lncRNA-XIST expression levels in cancer tissues were associated with a poorer overall survival. In the study conducted by Liu et al (22), 15 studies with a total of 920 patients were included in the meta-analysis, and the results suggested that high lncRNA-XIST expression levels were associated with distant metastasis, tumor stage and poor prognosis. However, a number of contrasting studies were published concerning the role of lncRNA-XIST in cancer: In a recent study by Du et al (18), lncRNA-XIST served as a tumor suppressor in prostate cancer, its expression correlating with prognosis and tumor stage.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the association between lncRNA-XIST expression and the survival rates of patients was not determined. However, recent studies revealed that high expression levels were correlated with decreased overall and disease-free survival (20,22,58). The subgroup analysis did not identify a source of heterogeneity, although significant heterogeneity in distant metastasis, tumor size and stage was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we observed that miR-7 could directly regulate RELA expression, as confirmed by the luciferase reporter assay. Since CD44 is tightly associated with the BCSC phenotype [10,16,34], we hypothesized that miR-7 decreased the BCSC subset mainly by targeting RELA to inhibit CD44 expression. Our findings agreed with a recent report by Cantley et al, which reported a targeted relationship between miR-7 and the NF-κB subunit RELA and miR-7 inhibition of RELA expression could impact the proliferation, invasion, and apoptosis of non-small cell lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“… 29 , 30 Many studies have reported that several lncRNAs could be used as prognostic biomarkers in human cancers, such as MALAT1, GAS5, XIST, and BLACAT1. 31 - 34 LncRNA NORAD is a novel identified lncRNA, located on Chr20q11.23. Lee et al first discovered that lncRNA NORAD could maintain genomic stability in human cells.…”
Section: Discussionmentioning
confidence: 99%